MATHEMATICS TEACHERS ASSESS INSTRUCTIONAL METHODS SUPPORTING KNOWLEDGE PROCESSES - Andreas M. Zendler; Cornelia Seitz; Dieter Klaudt (USN Kolaka, 2019)
Answers to the questions of which instructional methods are suitable for school, what instructional methods should be applied in teaching individual subjects and how instructional methods support the act of learning represent challenges to general education and education in individual subjects. This article focuses on the empirical examination of instructional methods supporting knowledge processes in the act of learning. A survey was conducted in which mathematics teachers evaluated 20 instructional methods in regard to the following knowledge processes: build, process, apply, transfer, assess and integrate. The results of the study demonstrate that certain instructional methods are especially predestined for mathematics education: problem based learning, direct instruction, learning at stations, learning tasks, project work and discovery learning